Survival assessment and pre-diagnostic risk factors for lung cancer incidence: Insights from the Golestan Cohort Study - Seyedeh Fatemeh Mousavi; Sahar Masoudi; Negar Rezaei; Farzad Pourghazi; Maryam Sharafkhah; Maysa Eslami; Akram Pourshams; Hossein Poustchi; Gholamreza Roshandel; Rasoul Aliannejad; Sadaf G. Sepanlou; Reza Malekzadeh (PLoS ONE, 2025)
Background Lung cancer remains a pressing health issue globally. This study investigates survival rates and the impact of pre-diagnostic factors on lung cancer incidence in Golestan Cohort Study (GCS). Method The GCS, initiated in 2004 with enrollment concluding in 2008, comprises 49,783 individuals aged 40–75 from the Golestan province in northeastern Iran. Our analysis included all cases of lung, tracheal, and bronchial cancers diagnosed under ICD-10 codes C33-C34 from the study’s inception to 2022, tracking participants until death. A sensitivity analysis, excluding lung cancer cases diagnosed within the initial 24 months of follow-up, was performed to address the reverse causation bias from previously undiagnosed conditions at baseline. Results Out of 49,783 participants in the study, 132 were diagnosed with lung cancer, of whom 130 died by the end of the study. The age and sex-standardized incidence rate stood at 20.39 per 100,000 person-years. The median survival post-diagnosis was approximately four months, with one-year and five-year survival rates at 18.67% and 1.56%, respectively. Sensitivity analyses identified advanced age, male sex, opiate use history, pack-years of cigarette smoking, and the utilization of non-gaseous energy sources as lung cancer risk factors. In contrast, high physical activity and a BMI of 25 or higher were inversely associated with lung cancer risk. Conclusion Our study highlights the critical burden and low survival rates of lung cancer in resource-limited regions. Mitigating key risk factors and enhancing access to diagnostic and treatment services through targeted public health policies and comprehensive strategies are essential for ensuring equitable healthcare and improving lung cancer outcomes for underserved populations.